2016
DOI: 10.1177/0883911515627473
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial efficacy of quaternized poly[bis(2-chloroethyl)ether-alt-1,3-bis[3-(dimethylamino)propyl]urea] against targeted pathogenic and multi-drug-resistant bacteria

Abstract: Here, we have investigated in vitro antimicrobial efficacy of a quaternized cationic polymer, poly[bis(2-chloroethyl)ether-alt-1,3-bis[3-(dimethylamino)propyl]urea] (polyquaternium-2), against gram-positive as well as gram-negative bacteria along with several multi-drug-resistant bacterial strains. The antimicrobial efficacy of this polymer was first tested against some clinical pathogens followed by microorganisms isolated from acne lesions. Interestingly, polyquaternium-2 exhibited significant antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…The cationization of cotton has been researched for more than 50 years (Correia et al 2020 ) but has grown especially at the beginning of the 2000s, after the after process improvement by Hauser and Tabba ( 2001 ). Besides, cationic cellulose is widely applied in other fields, such as papermaking (Gao et al 2016 ; Odabas et al 2016 , 2017 ; Aguado et al 2018 ), cosmetics (Bujak et al 2020 ), adsorbents (Pei et al 2013 ; Lawchoochaisakul et al 2021 ), flocculants (Yan et al 2009 ; Sirviö et al 2011 ) and antimicrobial agents (Chaker and Boufi 2015 ; Kumar et al 2016 ). Cationic agents are also used to prepare fabrics with functional properties, such as UV protection, hydrophobicity, and conductive textiles (Wang and Hauser 2010 ; Kamal Alebeid and Zhao 2015 ; Sahito et al 2015 , 2016 ; Abd El-Hady et al 2020 ; Liu et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cationization of cotton has been researched for more than 50 years (Correia et al 2020 ) but has grown especially at the beginning of the 2000s, after the after process improvement by Hauser and Tabba ( 2001 ). Besides, cationic cellulose is widely applied in other fields, such as papermaking (Gao et al 2016 ; Odabas et al 2016 , 2017 ; Aguado et al 2018 ), cosmetics (Bujak et al 2020 ), adsorbents (Pei et al 2013 ; Lawchoochaisakul et al 2021 ), flocculants (Yan et al 2009 ; Sirviö et al 2011 ) and antimicrobial agents (Chaker and Boufi 2015 ; Kumar et al 2016 ). Cationic agents are also used to prepare fabrics with functional properties, such as UV protection, hydrophobicity, and conductive textiles (Wang and Hauser 2010 ; Kamal Alebeid and Zhao 2015 ; Sahito et al 2015 , 2016 ; Abd El-Hady et al 2020 ; Liu et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it may be a candidate for cotton cationization. P42 has antimicrobial efficacy and non-toxic behavior reported (Kumar et al 2016 ). A sustainable approach with plasma treatment and cationization of cotton at the greige stage using P42 was recently reported by the same research group (Correia et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, the cationization of cellulose was performed by using a novel cationic agent: propyl]urea] quaternized (P42), also known as Polyquaternium-2. P42 is a commercially available hypotoxic cationic polymer, has antimicrobial activity and has been commonly used in the cosmetic industry (Chen et al 2016;Kumar et al 2016). The monomeric unit of P42 contains two quaternary ammonium groups, which is essential for cellulose cationization as it provides cationic groups (Roy Choudhury 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, based on these strategies, have been taken up and demonstrated their efficacy in the literature. [36][37][38][39][40][41][42][43] Recently, these concerns have also been addressed to an extent by conjugation with polyethylene glycol (PEG). Pegylation is one of the commonly used techniques to improve in vivo efficacy of peptides, proteins, and polymers.…”
Section: Introductionmentioning
confidence: 99%